Implementing Healthy School Programs to Foster Emotional Intelligence Development in Elementary Students: A Case Study of MIM PK Wirogunan - Dela Yuniati; Sukartono Sukartono (Papanda Publisher, 2026)
School health programs represent critical interventions for promoting student well-being, yet their influence on emotional intelligence development remains underexplored. This study examined the implementation of the Healthy School Program at MIM PK Wirogunan and its contribution to fostering emotional intelligence among elementary students. A qualitative case study design was employed, collecting data through semi-structured interviews with school principals, teachers, staff, and students, complemented by direct observations and documentary analysis. Data were analyzed using Miles and Huberman's interactive model, with triangulation techniques ensuring credibility and trustworthiness. The program successfully enhanced five emotional intelligence dimensions: self-awareness through environmental responsibility practices, emotion regulation via structured nutrition and rest schedules, motivation through active health participation, empathy through anti-bullying initiatives, and social skills through collaborative activities. Key supporting factors included clean school environments, nutritious meal provision, structured communal eating programs, policies prohibiting unauthorized snacking, and anti-bullying initiatives. Implementation barriers comprised resource limitations, insufficient parental involvement, inconsistent healthy behavior practices, inadequate sports facilities, teacher knowledge gaps, and absent evaluation mechanisms. The Healthy School Program effectively cultivates emotional intelligence through integrated health interventions, demonstrating that comprehensive school health approaches serve dual purposes addressing both physical well-being and social-emotional development. Successful implementation requires adequate resources, systematic teacher training, sustained community engagement, and age-appropriate program modifications.